Accessibility assessment for operation and maintenance of offshore wind farms in the North Sea. Issue 4 (15th September 2016) - Martini, Michele; Guanche, Raúl; Losada, Iñigo J.; Vidal, César
Abstract: Focused on offshore wind energy operation and maintenance applications, this work presents a detailed accessibility analysis of the North Sea. After a review of existing normative dedicated to inspection and access of offshore wind turbines, a rigorous mathematical formulation of relevant accessibility parameters is given by means of the set theory. Long‐term and high‐resolution metocean data are extracted from reanalysis databases and used to evaluate spatial and temporal variability of such parameters. Respectively restricted by significant wave height and mean wind speed, access by workboat and helicopter is evaluated. Being affected by both wave height and wind speed. Access by offshore crane is also analyzed. It resulted that the UK coast and the southern region of the North Sea are highly accessible, while the coast of Denmark and Norway undergoes more severe metocean conditions. This is, however, balanced by a higher wind resource. Moreover, a strong seasonality is ascertained, together with a drastic reduction of accessibility during daytime in a vast part of the basin. Accessibility during daytime in winter and autumn is very difficult for the whole North Sea. Among the studied farms, Dogger Bank is by far the one with the highest resource and lowest accessibility, while Thorntonbank III the one with the lowest resource and highest accessibility. In addition, accessibility is non‐linearly related to wind speed and wave height limits chosen for the access strategies covered. Copyright © 2016 John Wiley & Sons, Ltd.